MANAGERIAL PERFORMANCE EVALUATION OF THE PENCAK SILAT TEAM AT JAKARTA STATE UNIVERSITY BASED ON DATA ANALYSIS OF THE LAST FIVE YEARS - Eko Novian Saputro (Jurnal Gladiator, 2026)
This study aims to evaluate the managerial performance of the Pencak Silat Team at Universitas Negeri Jakarta (UNJ) based on a longitudinal data analysis covering the past five years (2020–2025). Despite consistently securing the general championship title at national student tournaments, a declining trend in gold medal acquisition necessitated an evaluative assessment. A descriptive mixed-methods approach (qualitative and quantitative) was employed, assessing managerial components such as organization size, coach-to-athlete ratios, and operational efficiency. Data triangulation included documentation of team performance, management structures, and open-ended organizational assessments. The efficiency ratio was calculated by comparing the total medals won against total human resources utilized (management staff, coaches, and athletes). Quantitative analysis indicated that while the highest total human resource engagement occurred in 2022 (95 personnel), the absolute efficiency peaked in 2025. In 2025, the team produced 14 medals with only 57 total personnel, yielding the highest efficiency index of 0.246, compared to the lowest efficiency index of 0.126 in 2024. Qualitative thematic reduction revealed that managerial effectiveness is primarily driven by structural work quality and division-specific competence rather than pure personnel volume. In conclusion, a leaner, highly coordinated management structure yields superior performance optimization, preventing role redundancy and enhancing athlete support systems. These findings serve as a strategic reference for collegiate sports management to maintain long-term championship sustainability.